THE URGENCY OF THE PRINCIPLE OF FAIRNESS OF BPJS KESEHATAN CONTRIBUTIONS FOR WAGE EARNERS (PPU) - Abidin, Zainal; Suroso, Dr Imam (jfpublisher, 2025)
This article discusses the urgency of applying justice principles within the contribution system of BPJS Kesehatan (Indonesia's National Health Insurance) for wage-earning workers. The study aims to examine how the principle of justice can be effectively implemented, given the discrepancies between the contribution provisions regulated under Presidential Regulation No. 64 of 2020 and the stipulations in Law No. 6 of 2023 concerning the Ratification of the Government Regulation in Lieu of Law (Perppu) on Job Creation into Law, specifically Article 81 point 31 and Article 90B paragraph (1).This research adopts a normative legal method, employing positive law analysis combined with the theory of justice as the analytical framework. The data were collected through literature review, focusing on statutory regulations and relevant academic studies. The findings reveal that the principle of justice in the BPJS Health contribution system for wage-earning workers can be realized through two main mechanisms. First, by applying the principle of equity, which entails adjusting contribution rates based on the business scale of the company, in accordance with the mandate of the Job Creation Law. Second, by adopting the principle of social justice, through the provision of subsidies or contribution assistance for workers employed in micro and small enterprises. This scheme aims to ensure that all workers have fair and equitable access to health insurance, without being disproportionately burdened by contribution obligations.